Individual taxation subject in non-accounting curriculum: perception of potential taxpayers - Mohd Noor, Ida Haryanti (2022)
Individual Taxation subject is one of the subjects compulsory to be taken by accounting students in tertiary education. Occasionally, this subject also needs to be enrolled by non-accounting students either as compulsory subject or elective subject. However, only few non-accounting courses that choose Individual Taxation subject to be included in its curriculum despite these students will become potential taxpayers in the future. Based on the empirical findings from prior researches, it is suggested that tax education is vital for the taxpayers. It can increase the level of tax understanding among taxpayers, therefore, will lead to higher tax compliance rate and subsequently increase the government’s revenues. Thus, it is very important that taxpayers are well acquainted with knowledge relating to tax principles and policies under the Malaysian taxation legislation. The purpose of this study are to investigate the non-accounting students' opinion on the importance of Individual Taxation subject at tertiary level and to identify the relevancy of introducing Individual Taxation subject at all faculties. By using online survey, the questionnaires were distributed among Bachelor of Corporate Administration’s students from Faculty of Administrative Science and Policy Studies who had enrolled Individual Taxation subject in Universiti Teknologi MARA Negeri Sembilan branch. The study found that majority of the students agreed that Individual Taxation subject is important at tertiary level. The study also found that majority of the students believed that Individual Taxation subject was relevant to all faculties, either to be offered as compulsory subject or elective subject. This finding implied that tax education has become important among non-accounting students as it would facilitate them later in computing income tax liability when they become liable later. Hence, there is a need to introduce Individual Taxation subject as formal learning at tertiary level. Therefore, it is suggested that educators should include taxation subject in course learning curriculum as basis to disseminate tax knowledge to students so that they will become a good and responsible citizens towards tax administrations especially under self assessment system.